Traumatic pasts : history, psychiatry, and trauma in the modern age, 1870-1930 - Lerner, Paul Frederick, 1966-; Micale, Mark S., 1957- (Cambridge, UK ; New York : Cambridge University Press, 2001)
Traumatic Pasts offers a variety of perspectives on mental trauma in war, medicine, culture, and society in modern European and American history. Its primary goals are: to provide a generous sampling of the best of the new historical scholarship about trauma; to indicate the empirical, analytical, and methodological scope of this work; and to present some of the conceptual and methodological issues inherent in writing about the subject. The book operates on the premise that the historical humanities have something crucially important to say about trauma; its essays may be read, in part, as attempts to introduce a deep historical dimension into present-day debates and controversies. However, it is important to stress that these essays are not simply addressed to current concerns; rather, they reflect a shared conviction that trauma opens up new perspectives in the study of social and cultural history.
Includes bibliographical references and index.
Keywords: Psychiatry -- History -- 19th century; Psychiatry -- History -- 20th century; Psychic trauma -- History; Boek